A biomechanical analysis of articular cartilage of the human elbow and a potential relationship to osteochondritis dissecans - Constantinides, Georgios; Athanasiou, Kyriacos A.; Schenck, Robert C (My University, 1994)
A cadaveric study of the articular surfaces of the radiocapitellar joint was undertaken to identify a biomechanical mechanism of osteochondritis dissecans of the humeral capitellum. The articulating radial head and capitellum of fresh anatomic specimens were dissected and tested for intrinsic mechanical properties. Significant differences exist in the mechanical properties and thickness of cartilage topographically in the capitellum and radial head, and between the two surfaces. The medial portion of the radial head is the softest of all radiocapitellar osteochondral segments tested. Comparing medial to lateral sites of the capitellum, there is a trend of decreased stiffness; lateral segments are softer than medial ones. The central section of the radial head is significantly stiffer than the lateral capitellum. There is no significant difference between the stiffness of the radial head sites and the medial capitellum. The disparity in the mechanical properties of the central radial head and lateral capitellum would increase strain in the lateral capitellum. During high- valgus stress activities such as throwing, this increased strain may be a factor in the initiation and localization of the dissecans lesion observed in osteochondritis dissecans of the elbow.
Keywords: Biomechanics; Analysis of variance; Middle age; Elbow Diseases